(3GdeNJQY aj afhf ef GdUfYs - (3YHO GdbOhS GdgGTejs
(3ChdgG (B:s
(3GdUfGYGJ hGdYdhe GdJWHjbjI djSJ ceG gh eYQha ef NUGFU CeI Ohf ZjQ gGHd gi ef NUGFU YUQ ajg JHK GdMVGQI s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg hQCjJ ajg ef GdCSQGQ GdafjI GdecfhRI eG dGjYQaI Cgd gPg GdUfGFY Edi GdCf s
(3GdfSNI eWHhYIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs